A researcher's guide to regression, discretization, and median splits of continuous variables1. Issue 4 (6th May 2015) - Rucker, Derek D.; McShane, Blakeley B.; Preacher, Kristopher J.
Abstract: We comment on Iacobucci, Posavac, Kardes, Schneider, and Popovich (2015) by evaluating the practice of discretizing continuous variables. We show that dichotomizing a continuous variable via the median split procedure or otherwise and analyzing the resulting data via ANOVA involves a large number of costs that can be avoided by preserving the continuous nature of the variable and analyzing the data via linear regression. As a consequence, we recommend that regression remain the normative procedure both when the statistical assumptions explored by Iacobucci et al. hold and more generally in research involving continuous variables. We also discuss the advantages of preserving the continuous nature of the variable for graphical presentation and provide practical suggestions for such presentations.